Office hysteroscopy and endometrial/cervical cancer: an update on their potential close relationship - Siristatidis, Charalampos; Basios, George; Makris, George-Marios; Salamalekis, George; Vogiatzi, Paraskevi; Papantoniou, Nikolaos; Bettocchi, Stefano (European Journal of Oncology and Environmental Health, 2016)
Aim To provide an insight on the applicability, efficiency and accuracy of office hysteroscopy (OH) in the diagnosis and potential treatment of endometrial (EC) and cervical cancer (CC) and their respective premalignant states. Materials and methods A literature update on the efficiency of OH in EC and CC, through a search strategy formed for PubMed. Results Endometrial hyperplasia and EC can be accurately and efficiently diagnosed with OH, especially when combined with endometrial sampling. The role of OH in the diagnosis of cervical intraepithelial neoplasia and CC is less investigated and remains supplementary to traditional modalities. Regarding the treatment of both gynecological cancers and their premalignant states, there are no data to support the utility of the technique. Conclusions The modern technological advances have promoted the evolution of sophisticated hysteroscopes and the respective techniques, with OH being an advanced approach in the visualization of the female genital tract with fine imaging along with specialized software utilities for advanced processing. Prospective cohort studies could add to its value with respect to resolving discrepancies arising from previous conflicting views on the specificity and sensitivity of the technique, and advanced clinical training, could establish OH as a first-line diagnostic procedure for the management of pre-malignant and malignant lesions in the near future.